Gastrointestinal Disease: New Diagnostic and Therapeutic Approaches - Beata Jabłońska; Sławomir Mrowiec (Biomedicines, 2023)
Gastrointestinal diseases (GIDs) involve various benign and malignant pathologies of the digestive tract, as well as the liver, biliary tract, and pancreas [...]